2017
DOI: 10.1111/deci.12295
|View full text |Cite
|
Sign up to set email alerts
|

Triggering Insight: Using Neuroscience to Understand How Priming Changes Individual Cognition during Electronic Brainstorming

Abstract: We build on prior theory and research on electronic brainstorming to examine how achievement priming influences individual cognition leading to changes in individual behavior and ultimately team performance. We conducted a repeated measures experiment using electroencephalography with 53 subjects performing two brainstorming tasks. We found that priming altered cognition in the left and right regions of the frontal cortex; that is, achievement priming triggered cognition in areas of the brain related to creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 95 publications
0
11
0
1
Order By: Relevance
“…Although growing evidence has suggested dissociations between conscious and unconscious processing in insight problem solving, it has been suggested the process of insight problem solving is largely governed by an implicit learning mechanism (Orita & Hattori, 2019;Suzuki & Fukuda, 2013). It has also been found that priming, which is a type of implicit learning, has a great impact on insight problem solving; individuals in a primed condition perform better than individuals in an unprimed condition in creative problem solving (Minas et al, 2018;Mumford et al, 2001).…”
Section: Priming Effect and Insight Problem Solvingmentioning
confidence: 99%
“…Although growing evidence has suggested dissociations between conscious and unconscious processing in insight problem solving, it has been suggested the process of insight problem solving is largely governed by an implicit learning mechanism (Orita & Hattori, 2019;Suzuki & Fukuda, 2013). It has also been found that priming, which is a type of implicit learning, has a great impact on insight problem solving; individuals in a primed condition perform better than individuals in an unprimed condition in creative problem solving (Minas et al, 2018;Mumford et al, 2001).…”
Section: Priming Effect and Insight Problem Solvingmentioning
confidence: 99%
“…An EBS has the potential to overcome many of the confounding factors for creativity in face‐to‐face brainstorming, such as social conformity (Liikkanen et al, 2011; Stroebe, Diehl, and Abakoumkin, 1992), social loafing (Buisine, Guegan, and Vernier, 2017), production blocking (Minas, Dennis, Potter, and Kamhawi, 2018), or evaluation apprehension (Gabriel, Monticolo, Camargo, and Bourgault, 2016). Furthermore, a well‐designed EBS provides a structured method for people who do not have access to trained design facilitators to assist in shaping and managing group processes as well as ensuring the completion of necessary methodological steps.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other tools measuring brain activities, EEG has two main advantages (Matukin et al, 2016). First, it is a noninvasive and relatively inexpensive technique (Minas et al, 2018). Second, EEG can measure electrical signals in submillisecond intervals, which has the highest temporal resolution among all the neuroimaging techniques (Minas et al, 2018).…”
mentioning
confidence: 99%
“…First, it is a noninvasive and relatively inexpensive technique (Minas et al, 2018). Second, EEG can measure electrical signals in submillisecond intervals, which has the highest temporal resolution among all the neuroimaging techniques (Minas et al, 2018). fMRI has a longer resolution time of several seconds (Boshoff, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation